Management of diabetes mellitus in people living with HIV: A single-center experience - Cattaneo, Dario; Gidaro, Antonio; Rossi, Antonio; Merlo, Andrea; Formenti, Tiziana; Meraviglia, Paola; Antinori, Spinello; Gervasoni, Cristina (Frontiers in Pharmacology, 2023)
Background: Diabetes mellitus (DM) is more common in people living with HIV (PLWH) than in HIV-negative patients. Here we aimed to describe the response of PLWH with DM to glucose-lowering therapies in a reference hospital of northern Italy. Setting: 200 PLWH and DM were identified from the database of our clinic. Methods: Good control of DM was defined as having fasting glucose <130 mg/dL or HbA1c <53 mmol/mol. Hypercholesterolemia was defined as being on a lipid-lowering medication and having low-density lipoproteins (LDL) >100 mg/dL. The distribution of glucose-lowering therapies in PLWH was compared with that of HIV-negative patients with DM. Results: Mean total fasting glucose and HbA1C were 143±50 mg/dL (51% exceeding the 130 mg/dL cutoff) and 51 ±16 mmol/mol (30% exceeding the 53 mmol/mol cutoff), respectively. PLWH were less treated with dipeptidyl peptidase-4 inhibitors (1.7% versus 9.6%, p<0.01) and sulfonylureas (3.3% versus 13.2%, p<0.01), being conversely more frequently treated with metformin (53.8% versus 37.7%, p<0.01), glifozins plus metformin (7.1% versus 2.0%, p<0.05) or insulin plus other glucose-lowering agents (5.5% versus 0.5%, p<0.01). Conclusions: These evidences suggest that a rationale selection of the best glucose-lowering and lipid-lowering agents for each antiretroviral therapy would improve the quality of life of PLWH.